Insect Crude Thoraxial Antigen-G Extracted from Apis mellifera to Enhance Serum Immunoglobulin of Goats: An Entomology Contribution in Animal Science - Toar, Wisje Lusia; Rumokoy, Laurentius; Untu, Ivonne Maria; Assa, Geertruida (ANIMAL PRODUCTION, 2018)
This research was conducted to evaluate the influence of insect crude thoraxial antigen-G (CTA) extracted from Apis mellifera L. (Hymenoptera: Apidae) to enhance goat’s serum immunoglobulin level. The first part of this study was the determination of insect CTA proportion level. The insects were collected from four different places: Tomohon, Minahasa, North-Minahasa and Manado areas. The second part of the study was the application of A. mellifera CTA substance on serum immunoglobulin level classification. In this part, twelve young goats handled with traditional maintenance.  The animals experiment were divided in two groups: control group and the other treated with 100 µg CTA extract. The proportion of serum immunoglobulins level of goats was detected at 14th days after immunization with insects CTA extract, and compared with the animals immunoglobulin levels at the starting day of treatment.  The data of CTA extract proportion level of the insects collected were subjected to statistically analysis using the general linear model (GLM) procedure of SPSS 22. Concerning the classification level of the animal treated with CTA was statistically analyzed according to Mann-Whitney test. The results showed that the proportion level of thoraxial antigens-G of A. mellifera from all areas observed were not significant different (P>0.05). This crude thoraxial antigens-G of this insect were able to increase serum antibody level of the experiment animal after 14 days of immunization. The immunoglobulin level qualification of animals in treated group were significant higher (P<0.05) than in control group. We concluded that the CTA extract of the Apis mellifera could be empowered to improve the young goat immunity against the pathogenic microbes in their environment.